Can family firms nurture socioemotional wealth in the aftermath of Covid-19? Implications for research and practice. Issue 3 (July 2021) - Firfiray, Shainaz; Gomez-Mejia, Luis R
Family firms are the most prevalent form of economic organization in the world, but despite their reputation for resilience and agility, many of them are facing enormous challenges due to the Covid-19 pandemic. In this essay, we examine how the pressures to respond to this health emergency are affecting the ability of family firms to preserve their socioemotional wealth (SEW). In addition, we also provide implications for family business research in a post-Covid world. JEL CLASSIFICATION: M10; M53; M54; L200; L210